After the New Left: U.S. cultural radicalism and the Central America solidarity movement, 1979-1992 - Witham, Nicholas David (2012)
After the New Left: U.S. Cultural Radicalism and the Central America Solidarity Movement, 1979-1992 examines how the work of intellectuals, journalists and filmmakers combined with that of transnational solidarity activists during the 1980s to negotiate the legacies of the U.S. New Left and create a radical anti-interventionist movement forged around opposition to the policies of the Reagan administration in Central America. The case studies examined include the revisionist historiography of Walter LaFeber and Gabriel Kolko, transnational debates about the meaning of "solidarity" in the pages of several important publications by Verso Books, antiinterventionist journalism at left-liberal magazine The Nation and radical weekly newspaper the Guardian, and political filmmaking including Haskell Wexler's Latino (1985) and Oliver Stone's Salvador (1986), as well as feminist documentaries When the Mountains Tremble (1983) and Maria's Story (1991). Detailed historical analysis of each case study casts light on the relationship that developed between cultural work and political activism during the 1980s, a relationship that helped to sustain the U.S. left through a long and difficult period of Republican ascendency, economic restructuring and decline in trade union militancy. Ultimately, whilst the individuals and institutions examined often used their work to provide representations of the ideas and impulses of the Central America solidarity movement, they also played a sometimes unanticipated role in the constitution of antiinterventionist politics. In other words, the cultural work of intellectuals, journalists and filmmakers played a role not only in reflecting political processes, but also in helping to shape them. Analysis of the uses to which U.S. cultural radicalism was put in the immediate period "after the New Left" therefore provides an excellent opportunity not only to engage with the complex legacies of 1960s radicalism in recent American history, but also to rethink the question of the relationship between radical culture and activist politics.